Antipsychotic treatment of psychotic disorders in forensic psychiatry: patients' perception of coercion and its predictors - Horvath, Juliane; Steinert, Tilman; Jaeger, Susanne (International journal of law and psychiatry, 2018)
Background - Despite the major encroachment of coercive measures on the fundamental rights of affected forensic psychiatric patients, there is relatively few research done in this field. Considering the relevance of this subject for psychiatric care and the recent changes of the legal basis of coercive treatment in Germany, more studies are needed. The present study examines forensic psychiatric inpatients' perception of coercion regarding the prescribed antipsychotic medication and factors associated with the perception of coercion. - Material and methods - Patients with schizophrenia, schizotypal and delusional disorders in two forensic psychiatric institutions in Southern Germany were interviewed about their experience of coercion related to antipsychotic medication. Due to a lack of appropriate psychometric scales, the perception of coercion regarding antipsychotic medication was assessed using an adapted version of the MacArthur Admission Experience Survey (aAES). The influence of sociodemographic and illness-related factors, of the attitude towards medication, insight into illness and symptom severity on the extent to which patients felt coerced to take the prescribed medication was analyzed. Two Visual Analog Scales, the Drug Attitude Inventory DAI-10, the Positive and Negative Syndrome Scale PANSS, the Fragebogen zur Krankheitseinsicht (Questionnaire about insight into illness) FKE-10 and the Coercion Experience Scale CES were used as psychometric scales. - Results - 50% of all patients eligible for the study gave their written consent. 70% of all participants had experienced coercive measures between admission and time of data assessment. The DAI-10 and the aAES correlated moderately, a high level of insight into illness being correlated to less perceived coercion. The FKE-10 and the aAES correlated moderately as well, a high level of insight into illness being correlated to less perceived coercion. The severity of symptoms (PANSS score) and the level of perceived coercion (aAES score) correlated weakly, participants with more severe symptoms perceived more coercion than those with less marked symptoms. A linear regression model showed that to what extent patients felt coerced to take the prescribed antipsychotic medication was mainly influenced by their attitude towards medication and the degree of insight into illness, to a lesser extent by symptom severity (R2=0.565, p<0.001). Sociodemographic factors were not related to the extent to which patients felt coerced to take the antipsychotic medication. - Conclusions - Predictors of the experience of coercion related to the prescribed antipsychotic medication of forensic psychiatric inpatients with schizophrenia and related disorders are not so much sociodemographic or illness-related factors as education or past medical history, but rather potentially influenceable variables such as insight into illness or attitude towards medication.
Gesehen am 11.09.2019